Public law rationing of the circulation of foreign exchange gold and investment gold (Discourse of Law and Administration, 2025)
The purpose of the study is to discuss the issue of public-legal rationing of trade in foreign exchange and investment gold. The study discusses selected provisions of the Probate Law, the Foreign Exchange Law, the Law on Goods and Services Tax and the Law on Counteracting Money Laundering and Terrorist Financing. The thesis is formulated that the rationing of trade in foreign exchange and investment gold should ensure the security of trade, while protecting the fiscal objectives of the State. However, it is necessary to shape the record-keeping and control instruments in such a way as not to violate the confidence of the administered in the state authorities and limit the grey market.  The provisions of the Foreign Exchange Law were assessed positively. It has been proposed to consider legislative changes limiting record-keeping obligations in the trading of investment gold. The concept of foreign exchange gold and investment gold was comprehensively discussed, noting the differences between the definitions.
Keywords: investment gold; foreign exchange gold; foreign exchange law